In silico retrieval of sulfiredoxin from Setaria italica, Panicum miliaceum, and Eleusine coracana: Sequence characterization, structural modeling, and protein–protein interaction analysis - Rahul Thakur; Arvind Gupta; Kanchan Rauthan; Deepti Dixit; Arzoo Choudhary; Ashutosh Kumar Pandey; Atul Krishna Dev; Saurabh Yadav (Plant Gene, 2026)

Saturated steam-assisted texturized plant protein as a sustainable and physicochemically comparable alternative to boneless chicken breast - Kannan Vignesh; Dadasaheb Wadikar; Dev Kumar Yadav; Atul Kumar; Phani Kumar Garlapati; Johnsy George; Aisha Tabassum; R. Kumar (International Journal of Gastronomy and Food Science, 2026)

A numerical study on breakup of a liquid jet in an axial electric field - Dev S. Hathi; Pratik M. Panchal; Atul Sharma; Rochish Thaokar; Absar M. Lakdawala (Journal of Aerosol Science, 2023)

Carps, Catla catla, Cirrhinus mrigala and Hypophthalmichthys molitrix Are Resistant to Experimental Infection with Tilapia Lake Virus (TiLV) - Pravata Pradhan; Dev Verma; Shrish Yadav; Atul Dev; Thangaraj Swaminathan; Anutosh Paria; Rajendran Valappil; Neeraj Sood (Fishes, 2021)
Tilapia tilapinevirus, also known as tilapia lake virus (TiLV), is an emerging fish virus that primarily affects tilapines. However, the virus has also been detected in a few non-tilapines. As tilapia is generally farmed in polyculture systems along with carps in South Asian countries, there is a likelihood that TiLV-infected tilapia can transmit the virus to the co-cultured species. In view of the above, the susceptibility of three carp species, namely catla (Catla catla), mrigal (Cirrhinus mrigala) and silver carp (Hypophthalmichthys molitrix) was evaluated vis-à-vis tilapia, following experimental infection with TiLV. No clinical signs and histopathological alterations could be observed in carps. RT-qPCR revealed that TiLV copy numbers in liver and brain of all the three carps were almost negligible and did not show any increase with time, suggesting that the virus did not replicate in liver and brain, the target organs of TiLV. Further, TiLV could not be isolated from pooled liver and brain tissues of carps using permissive CFF cell line. On the contrary, in tilapia, typical clinical signs and histopathological lesions were observed and there was significant increase in TiLV copy number up to 6 days post-injection. Furthermore, the virus was successfully isolated from pooled liver and brain tissue of infected tilapia. From the above findings, it could be concluded that C. catla, C. mrigala and H. molitrix are resistant to TiLV infection and unlikely to be carriers for this virus.

Nanosensors and nanobiosensors in food and agriculture - Anup K. Srivastava; Atul Dev; Surajit Karmakar (Environmental Chemistry Letters, 2018)

Nanomaterial toxicity for plants - Atul Dev; Anup Kumar Srivastava; Surajit Karmakar (Environmental Chemistry Letters, 2018)

A Quantitative Measure of Conformational Changes in Apo, Holo and Ligand-Bound Forms of Enzymes - Satendra Singh; Atul Kumar Singh; Gulshan Wadhwa; Dev Bukhsh Singh; Seema Dwivedi; Budhayash Gautam; Pramod W. Ramteke (Interdisciplinary Sciences: Computational Life Sciences, 2016)

A quantitative measure of conformational changes in Apo, holo and ligand bound form of enzymes - Satendra Singh; Atul Kumar Singh; Gulshan Wadhwa; Dev Bukhsh Singh; Seema Dwivedi; Budhayash Gautam; Pramod W. Ramteke (Interdisciplinary Sciences: Computational Life Sciences, 2015)